ANALISIS FAKTOR-FAKTOR PEMASARAN JASA TRANSPORT LAUT YANG DIPERTIMBANGKAN PENUMPANG DALAM MEMBUAT KEPUTUSAN MEMILIH JASA PENYEBERANGAN KAPAL CEPAT LINTAS SURABAYA BANJARMASIN - Nurul Widyawati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
The objective of the study in PT Angkutan Sungai Danau dan Penyeberangan/ ASDP (Persero) is to examine passengers’ decision to choose sea transportation of Surabaya-Banjarmasin and to examine dominant factors of these. The population are passengers who used sea transportation of Surabaya-Banjarmasin, and the sample are 170 passengers. By using factors analysis in analysing the data, this study found 10 new factors. And by using multiple regression, this study found that 10 factors have influence in decision, and existence of agency are most influence in decision to choose sea transportation of Surabaya-Banjarmasin. R square value is 90,2%. It is mean that 90,2% of decision making influenced by factors in the model, remain 9,8% others